2019
DOI: 10.1029/2019gl082500
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Subsurface Pathways of Fukushima Cesium in the Northwest Pacific

Abstract: Advective pathways for Fukushima Daiichi Nuclear Power Plant (FDNPP)‐derived cesium observed in 2013 at 166°E south of the Kuroshio Extension (KE) at >500 m on the 26.5σθ isopycnal are investigated. Attention is paid to the KE's role in shaping these pathways. Using a high‐resolution model, particle trajectories were simulated backward and forward in time on 26.5σθ between the 2013 observations and the 2011 source. A large fraction of backtracked trajectories interacted with the mixed layer just offshore of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 42 publications
2
5
0
Order By: Relevance
“…Dynamics of floating tracers is fundamentally different from the dynamics of passive tracers, because in the former case, the tracer density on fluid particles changes due to the experienced surface‐velocity divergence, whereas in the latter case, it is materially conserved and only advected by the flow. In other words, the floating‐tracer density is compressible and can not be fully described by concentrations of Lagrangian particles—this fundamental theoretical issue escaped attention of many previous studies that dealt with the Lagrangian transport on the ocean surface (Cedarholm et al, ; Olascoaga et al, ; Prants et al, ; Wang et al, ). Physical mechanisms leading to formation of clusters can be different and overall remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Dynamics of floating tracers is fundamentally different from the dynamics of passive tracers, because in the former case, the tracer density on fluid particles changes due to the experienced surface‐velocity divergence, whereas in the latter case, it is materially conserved and only advected by the flow. In other words, the floating‐tracer density is compressible and can not be fully described by concentrations of Lagrangian particles—this fundamental theoretical issue escaped attention of many previous studies that dealt with the Lagrangian transport on the ocean surface (Cedarholm et al, ; Olascoaga et al, ; Prants et al, ; Wang et al, ). Physical mechanisms leading to formation of clusters can be different and overall remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the cooling seasons were the main focus, because the NPSTMW is formed and subducted into the subsurface layer during the cooler seasons. To investigate the pathways of the particles during the NPSTMW subduction, the particles within the mixed layer were analyzed after they were released, similar to Cedarholm et al (2019) who investigated the particles entering the mixed layer near the FDNPP via backward tracking on the 26.5s q isopycnal surface, which is outside of the NPSTMW density range (25.0-25.5s q ), from 166°E, 30°N using the HYCOM data from March 2011 to April 2013. The mixed layer depth (MLD) was defined as the thickness of the mixed layer where the vertical density gradient ( − ∂ r ∂ z ) is less than 3.0 × 10 -3 kg m -4 , which is consistent with the criterion of PV (2.0 × 10 -10 m -1 s -1 ) for NPSTMW.…”
Section: Particle Tracking Model and Experimentsmentioning
confidence: 99%
“…Subducted radioactive materials within the NPSTMW spread into the subtropical region of the North Pacific (Men et al, 2015;Cedarholm et al, 2019;Lee et al, 2023). Men et al (2015) reported that 134 Cs was found at 21.50°N, 125.00°E at a depth of 200 m near Taiwan Island after monitoring the area between 2011 and 2014.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dynamics of floating tracers is fundamentally different from the dynamics of passive tracers, because in the former case the tracer density on fluid particles changes due to the experienced surface-velocity divergence, whereas in the latter case it is materially conserved and only advected by the flow. In other words, the floating-tracer density is compressible and can not be fully described by concentrations of Lagrangian particles -this fundamental theoretical issue escaped attention of many previous studies that dealt with the Lagrangian transport on the ocean surface (Cedarholm, Rypina, Macdonald, & Yoshida, 2019;Olascoaga et al, 2013;Prants, Budyansky, & Uleysky, 2018;Wang, Olascoaga, & Beron-Vera, 2015). Physical mechanisms leading to formation of clusters can be different and overall remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%